2021
DOI: 10.1002/adfm.202105882
|View full text |Cite
|
Sign up to set email alerts
|

Visibly Clear Radiative Cooling Metamaterials for Enhanced Thermal Management in Solar Cells and Windows

Abstract: The study of transparent daytime radiative cooling with no additional energy consumption is a promising area of research. Its applications include solar cells and building and automobile windows that are prone to heating issues. Ubiquitous applications necessitate the development of metamaterials with high mechanical flexibility in a scalable manner while overcoming translucence. In this study, visibly clear and flexible radiative cooling metamaterials have been developed using a newly designed optical modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 45 publications
1
64
0
Order By: Relevance
“…Reproduced with permission. [403] Copyright 2021, Wiley-VCH. d) Illustration of concentrated PV system with Fresnel lens concentrators and an enclosure.…”
Section: Sub-bandgap Reflection In Pvmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [403] Copyright 2021, Wiley-VCH. d) Illustration of concentrated PV system with Fresnel lens concentrators and an enclosure.…”
Section: Sub-bandgap Reflection In Pvmentioning
confidence: 99%
“…On the stability aspect, the coverage of Si SCs with this metamaterial allowed a slower thermal degradation by 1.5× after 100 min of light soaking. [403] Recently, Heo et al compared the performance dependence of micrograting design-based radiative cooler for various PV technologies. [418] It was revealed that multi-junction SC technologies take the highest benefit of radiative cooling, with a temperature reduction of ≈6 °C compared to conventional glass-mounted baseline in outdoor environment under direct sunlight of ≈900 W m −2 .…”
Section: Passive Radiative Cooling Of Pvmentioning
confidence: 99%
See 1 more Smart Citation
“…Daytime radiative cooler (DRC), firstly proposed by Raman,4 consumes no electricity to reduce the temperature of objects below that of ambient air, the so-called sub-ambient cooling, by strongly reflecting the solar irradiance at l = 0.3-4 µm and simultaneously radiating heat out to the extremely cold universe through an atmospheric transparency window at l = 8-13 µm. 5 A variety of DRCs have been demonstrated, which are promising for potential applications in energy-efficient buildings, 6 photovoltaic modules, 7 and personal thermal management. 8 However, the majority of the proposed DRC materials exhibit white or metallic colors for guaranteeing a strong reflection of the solar irradiance, 9 which is unfavorable to some application scenarios and installation locations such as building envelopes 10 and vehicles 11 with aesthetic purposes and potentially leads to light pollution and eye safety issues.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30] There have been few works in terms of passive heat management techniques, such as metamaterials, graphene/Ag hybrid film, and SiO 2 particles, to mitigate the adverse thermal effects. [30][31][32][33] These nanostructures and nanostructured films (nanocrystalline, nanoporous, core-shell, nanocomposites, nanowires, nanorods, and QDs) may be artificial designs or nature-inspired designs from plants (epidermal cell of leaves of shade adapted plants), insects (moth-eye and butterfly wings) and other organisms (bacterial chlorosomes). 1,34 Various fabrications methods have been exploited to study the effect of nanostructures, including physical and chemical deposition techniques, namely nanoimprint lithography, 35,36 electrodeposition, 37 soft imprinting method, 38 rapid ion etching, 38 magnetron sputtering, 39 chemical vapor deposition 40 and many other different techniques.…”
Section: Introductionmentioning
confidence: 99%